Relationship between melatonin hormone and lipid profile of patients with myocardial infarction in Thi-Qar Governorate - Sami Daiekhmin; Khalid G. Al-Fartosi (University of Thi-Qar Journal of Science, 2022)
The present study was designed to detect the relationship between melatonin hormone and lipid profile in patients with myocardial infarction (MI) .The results showed that there was no significant difference in the level of melatonin in all MI patients, men and women patients compared with the control group. Additionally the results indicated that there was no significant difference of melatonin in men patients compared with women patients. Moreover, results indicated that there was a significant increase in levels of TG and LDL in patients compared with the control group. The results showed that there was no significant difference in level of TC, HDL and VLDL in MI patients compared with control group. Meanwhile, the results indicated that there was no significant difference in level of TC,HDL, TG, LDL and VLDL in women patients and men patients compared with control group. Furthermore the results showed that there was no significant difference in the level of TC, TG, VLDL and HDL in men and women patients when they compared between them, while showed significant increase in the level of LDL in women patients compared with men patients.